Hi Bunuel,

Could you please elaborate a little on Bold part.

(2) m=−nm=−n. Now,

if for example m=3=−(−3)=−nm=3=−(−3)=−n then the lines are not perpendicular but if m=1=−(−1)=−nm=1=−(−1)=−n,

So do you mean to say in the second case when we put the value in the reciprocal equation that is essential for perpendicular condition m*n=3*(-3)=-9 which is not the reciprocal i.e equal to -1. But in the case of 1 and -1 it is.

_________________

--------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------

When nothing seem to help, I would go and look at a Stonecutter hammering away at his rock perhaps a hundred time without as much as a crack showing in it.

Yet at the hundred and first blow it would split in two.

And I knew it was not that blow that did it, But all that had gone Before.